Photodynamic Therapy of Lung Cancer With Bronchial Artery Infusion of Photofrin. Issue 4 (1996) - Okunaka, Tetsuya; Kato, Harubumi; Konaka, Chimori; Furukawa, Kinya; Harada, Masahiko; Yamamoto, Yutaka
Abstract : Photodynamic therapy (PDT) utilizing Photofrin is proving to be effective for the treatment of early stage lung cancer. However, wider clinical applications of Photofrin as a photosensitizer for various cancers are hampered by potentially serious and prolonged skin photosensitivity. To prevent these side effects and reduce the hospitalization period, we recently gave reduced doses of Photofrin by bronchial arterial infusion. Five patients with endoscopically evaluated minimally invasive carcinoma of the lung were given 0.7 mg/kg of Photofrin by bronchial arterial infusion 48 hr before PDT. Complete remission was obtained in all 5 cases and no case showed skin photosensitivity when exposed to sunlight under careful surveillance at one week after PDT.